Examining differences in suicidality between and within mental health disorders and sexual identity among adults in the United States - David Adzrago; Ikponmwosa Osaghae; Nnenna Ananaba; Sylvia Ayieko; Pierre Fwelo; Nnabuchi Anikpezie; Donna Cherry (AIMS Press, 2021)
Background: Suicide is a leading but preventable cause of death and is preceded by domains of thoughts, plans, and attempts. We assessed the prevalence of suicidality domains and determined the association of suicidality domains with sexual identity, mental health disorder symptoms, and sociodemographic characteristics. Methods: We used the 2019 National Survey on Drug Use and Health (NSDUH) data to perform weighted multivariable logistic regression and margins analyses to examine between and within-group differences in suicidality by sexual identity among adults aged ≥ 18 years. Results: About 4.89%, 1.37%, and 0.56% of the population experienced suicidal thoughts, plans, and attempts, respectively. Those aged 18-25 years old had a higher odds of suicidality compared to those aged 26 years or older. Compared to those who reported having no alcohol use dependence, illicit drug use dependence, and major depressive episodes (MDEs), those who reported alcohol use dependence, illicit drug use dependence, and MDE had higher odds of suicidal thoughts, plans, and attempts. Between all sexual identity groups, bisexuals who experienced MDEs had the highest probability of having suicidal thoughts while lesbians and gays who experienced MDE showed a higher probability of suicidal plans and attempts compared to heterosexuals. Within each sexual identity group, the probability of having suicidal thoughts, suicidal plans, and suicidal attempts was higher for those who had experienced MDEs compared to those who had not experienced MDEs. Conclusion: Substance use disorder and MDE symptoms were associated with increased suicidality, especially among young adults and sexual minority people. This disparity underscores the need for tailored interventions and policies to enhance the provision of prompt mental health screening, diagnosis, and linkage to care for mental health services, particularly among the most vulnerable in the population.